INNOVATION IN ISLAMIC EDUCATION MANAGEMENT: ENHANCING TEACHER’S PROFESSIONALISM AND TECHNO-PEDAGOGICAL SKILLS - Astuti, Ruli; Siswanto, Siswanto; Walid, Muhammad (Antis Publisher, 2024)
This study explores the integration of technology in Islamic education management and its impact on enhancing teacher professionalism, particularly techno-pedagogical competence, in the digital era. Objective: The research aims to examine innovative strategies for improving the management of Islamic education and fostering teacher professionalism to meet the challenges of the digital age. Methods: A literature review approach was employed, synthesizing findings from various academic sources to highlight key developments, challenges, and opportunities in Islamic education management and teacher development. Results: The findings reveal that effective integration of technology enhances educational efficiency, quality, and access to resources while fostering innovative teaching methods and collaborative environments. Teacher professionalism is critical for achieving educational goals and is supported by strategies such as training, digital literacy programs, and professional development initiatives tailored to align with Islamic principles. The role of school administrators and government in facilitating these advancements is also significant. Novelty: This study contributes to the discourse on Islamic education by emphasizing the dual role of technology in administrative management and pedagogical enhancement. It underscores the necessity for holistic strategies to prepare educators for a digitally driven educational landscape, ensuring that Islamic educational institutions remain relevant, innovative, and aligned with their religious and moral values.